Menakar Esensi Waris Bilateral Analisis Pemikiran Hazairin - Riski Ramadhan; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
The Qur'an and Hadith explicitly outline the procedures and shares in Islamic inheritance law. The majority of Islamic scholars (jumhur ulama) agree that the verses concerning inheritance (fara'id) are qat’i (definitive), meaning they are not open to reinterpretation. As a result, many Muslims believe that the laws of inheritance are immutable, with little room for reform—particularly the rule that grants males twice the share of females (2:1), which is widely regarded as absolute. However, not all Muslims share this rigid view. Some scholars argue that Islamic inheritance law may be subject to change in response to evolving social contexts. Social conditions can influence the implementation of legal rulings, including those governing inheritance. In this context, Hazairin’s perspective offers an insightful interpretation of inheritance in Islam. He emphasizes that the Qur'an and Sunnah do not prescribe a specific kinship structure. Given the diversity of kinship systems—patrilineal, matrilineal, and bilateral—across Muslim communities, Hazairin argues that Islamic inheritance law must be flexible enough to adapt to these varying social realities. His approach integrates traditional values with Islamic legal principles, offering a nuanced model for inheritance distribution within the Indonesian context.